Polsko-chińska współpraca gospodarcza po przystąpieniu Polski do Unii Europejskiej - Kalinowska, Izabela (Gospodarka w Praktyce i Teorii, 2011)
The aim of the article is to analize polish-chinese economic relations after polish accession to the European Union structures. Studies carried out in the first part of the article concern trade rates between the two countries. Results show that polish import from China exceed export. The negative trends persist for many years and are continually deepening. From the geographical side, polish import from China flows mainly from the east coast part of China including Peking and Ningxia province. Polish export to China flows mainly to eastern and northern parts of the country. Concerning the commodity structure of the Polish-Chinese exchange, after the polish accession to the UE, polish products turned to be seen as high-quality as well as cheaper than in other UE countries. In 2009, electromechanical products accounted for more than 50% of the imported wares. Metallurgical, electromechanical and chemical products summed up to more than 76% of the polish export to China. The next part of the article analizes chinese investments in Poland and polish investments in China. In the end of 2007, chinese investments in Poland exceeded 120 mln USD. The biggest investments in Poland include building distribution center of GD Poland, Min Hoong Development company and TTL Poland – production center of TV LCD. In 2006, the polish investments in China reached 174 mln USD, investments included building Chinese-Polish Joint Stock Shipping Corporation “Chipolbrok” as well as Shanghai-Gdynia International Transportation Agency Co., Ltd. The last part of the article moved on to the topic of economic cooperation and barriers in access to Chinese market that include tariff and non- tariff barriers. To non-tariff barriers belongs: bureaucracy, weak protection of intellectual property rights as well as communication (language barrier).